2021
DOI: 10.21873/anticanres.15146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of PLA2G2A Expression in Gastric Cancer Patients who Receive Gastrectomy and Adjuvant S-1

Abstract: Background/Aim: This study aimed to evaluate the prognostic significance of PLA2G2A expression in patients with locally advanced gastric cancer (GC). Patients and Methods: PLA2G2A expression levels in cancerous tissue specimens and adjacent normal mucosa obtained from 134 patients with stage II/III GC who received adjuvant chemotherapy with S-1 after curative resection were measured using real-time quantitative polymerase chain reaction. Subsequently, the associations of PLA2G2A expression with clinicopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…When seeking the possible candidate(s) in our study, PLA2G2A emerged and was regarded to interact with Stachydrine in BC. On the basis of the existing documents, we summarized that PLA2G2A is indeed associated with assorted types of malignancies like prostate cancer, gastric cancer, and most importantly, BC (Chen et al., 2017; Hatori et al., 2021; Jespersen et al., 2021; Ozturk et al., 2020). However, there is a paucity of knowledge concerning the specific effects of PLA2G2A in BC, apart from an existing study suggesting a subtype of PLA2G2A + cancer‐associated fibroblasts enriched in HER2 + BC patients that promotes immune infiltration (Liu et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When seeking the possible candidate(s) in our study, PLA2G2A emerged and was regarded to interact with Stachydrine in BC. On the basis of the existing documents, we summarized that PLA2G2A is indeed associated with assorted types of malignancies like prostate cancer, gastric cancer, and most importantly, BC (Chen et al., 2017; Hatori et al., 2021; Jespersen et al., 2021; Ozturk et al., 2020). However, there is a paucity of knowledge concerning the specific effects of PLA2G2A in BC, apart from an existing study suggesting a subtype of PLA2G2A + cancer‐associated fibroblasts enriched in HER2 + BC patients that promotes immune infiltration (Liu et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, targeting arachidonic acid (AA) pathway (a metabolic process playing key roles in carcinogenesis) and its metabolic enzymes including Phospholipase A 2 s (PLA 2 s) by natural products can be a possible way for cancer prevention and therapy (Yarla et al., 2016). As a member of the PLA 2 s enzymes that are small lipolytic hydrolases with the capability to modulate immune responses via generating AA, PLA2G2A is related to different types of malignancies, like prostate cancer, gastric cancer, and most importantly, BC (Chen et al., 2017; Hatori et al., 2021; Jespersen et al., 2021; Ozturk et al., 2020). A previous study showed that PLA2G2A is the most clinically relevant enzyme producing extracellular AA, and AA contributes to unfavorable clinical outcomes in ovarian cancer by affecting the phenotype of tumor‐associated macrophages (Dietze et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As the family member of phospholipase A2 (PLA2), PLA2G2A and PLA2G4A have a variety of biological functions, such as the involvement of cell signaling and in ammatory response [36,37]. PLA2G2A and PLA2G4A have also found to be involved in the pathogenesis of cancer, such as gastric cancer, colorectal cancer, prostrate cancer, and so on [38][39][40][41]. Some studies have found that the expression of PLA2G2A gene in the mice can be suppressed by thyroid hormone [42,43].…”
Section: Discussionmentioning
confidence: 99%